2005
DOI: 10.1016/j.femsle.2004.12.017
|View full text |Cite
|
Sign up to set email alerts
|

The chloramphenicol resistance genecmlAis disseminated on transferable plasmids that confer multiple-drug resistance in swineEscherichia coli

Abstract: A recent study of beta-hemolytic Escherichia coli isolated from diarrheic swine found that 53% were resistant to chloramphenicol, a drug that has been prohibited from use in food animals in the US since the mid-1980s. To identify the factors governing the persistence of chloramphenicol resistance in the absence of specific selection pressure, the location of the chloramphenicol resistance gene cmlA and its linkage to other resistance determinants were investigated. Southern blot analysis of plasmid DNA from 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
81
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 28 publications
13
81
2
1
Order By: Relevance
“…In addition, having genes conferring resistance to multiple drugs was significantly associated with being multiresistance (p<0.01). Twenty-two percent of the Salmonella isolates were nega- aadA1 (6), aadA2 (6), aadB (6), bla TEM (6), cmlA (6), strA (2), strB (2), sul1 (3), sul2 (1), sul3 (6), tetA (6), tetB(2) AMP, CHP, SPC, STR, SUL, TET, TRI 11 (6.0) aadA1 (10), aadA2 (1), bla PSE-1 (5), bla TEM (9), cmlA (8), dfrA10 (1), dfrA12 (5), strA (9), strB (9), sul1 (6), sul2 (3), sul3 (9), tetA (8) tive to all the resistance genes tested, even through most of these isolates were resistant to at least one antimicrobial agent (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, having genes conferring resistance to multiple drugs was significantly associated with being multiresistance (p<0.01). Twenty-two percent of the Salmonella isolates were nega- aadA1 (6), aadA2 (6), aadB (6), bla TEM (6), cmlA (6), strA (2), strB (2), sul1 (3), sul2 (1), sul3 (6), tetA (6), tetB(2) AMP, CHP, SPC, STR, SUL, TET, TRI 11 (6.0) aadA1 (10), aadA2 (1), bla PSE-1 (5), bla TEM (9), cmlA (8), dfrA10 (1), dfrA12 (5), strA (9), strB (9), sul1 (6), sul2 (3), sul3 (9), tetA (8) tive to all the resistance genes tested, even through most of these isolates were resistant to at least one antimicrobial agent (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of chloramphenicol resistance and the existence of the chloramphenicol resistance gene (s) among E. coli isolates has been demonstrated [2,27] even through the antibiotic has been prohibited for using in domestic animals. This is in agreement of the results in our study, which the cmlA gene was found in the majority of chloramphenicol-resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies in Tanzania and Nigeria reported that, chloramphenicol is irrationally used in animals as evidenced by the presence of its residues in poultry and poultry products (Nonga et al, 2010;Darwish et al, 2013). However, it may be due to transfer of resistant genes as a result of cross contamination between humans, animals and the environment (Bischoff et al, 2005;Salehi and Bonab, 2006) or use of other antibiotics belonging to aphenicol group (Ruzauskas et al, 2009). The susceptibility pattern of E. coli from all the sampling sites is summarized in the Table 2.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Most prescriptions contained either one single antimicrobial substance or a combination of two antimicrobials that complement each other (Regula et al, 2009). However, more than 500 prescriptions of a triple combination of sulphonamide, tetracycline and a macrolide were observed, which is likely to select for multidrug-resistant bacteria (Bischoff et al, 2005;Matter et al, 2007). Another study on prescription pattern in Switzerland shown the largest number of treatments with a dosage above two times the recommended maximum dose in sheep and goats, where group treatment is common (Regula et al, 2009).…”
Section: Possible Causes Of Indiscriminate Use Of Antibioticmentioning
confidence: 99%